Polarization dynamics of Pi2 pulsations at midlatitudes during development of substorms in the auroral zone - Rakhmatulin R.A.; Pashinin A.Yu. (Solar-Terrestrial Physics, 2018)
We examine the changes in the orientation of the major axis of the polarization ellipse of irregular geomagnetic pulsations Pi2, observed at midlatitudes during a substorm disturbance developing in the auroral zone of the Russian Arctic sector. We have found the dependence of the polarization ellipse orientation on the longitude of a corresponding substorm. The results of current studies are compared with earlier results of similar studies using materials on the North American continent. We have concluded that the results are similar in general, with a slight discrepancy which may be due to peculiarities of the geological structure of the earth crust in the Russian Arctic sector.